SOME ASPECTS OF ADVOCATES ACTIVITY IN FOREIGN COUNTRIES - Matkarimov Kudrat Kalandarovich (Modern American Journals, 2026)
This article examines some aspects of advocates activity in foreign countries. The procedure and specific features of obtaining the status of advocate in foreign countries. According to the legislation of the Republic of Uzbekistan, citizens of the Republic of Uzbekistan can engage in advocacy. Therefore, it is necessary to give foreign lawyers an opportunity to practice professional activities in the Republic of Uzbekistan. Opinions and comments on the possibility of achieving positive results in the provision of legal assistance and legal consulting services were expressed.
Keywords: The concept of advocacy, legal aid and legal consulting services, rule of law, human rights, trustee, protected person.